Preliminary Study of CST in Malaysia based on Field Optical Efficiency - Saleman, Abdul Rafeq; Zulfattah, Z. M.; Najib, M. Ali; Rody, M. Z. M; Fadhli, Syahrial; Abdollah, Mohd Fadzli bin; Hanafi, M.H.M (Elsevier, 2013)
Solar is one of the many sources of renewable energy, and Concentrating Solar Tower (CST) is one of the most potential technologies in extracting solar energy. Thermal efficiency of CST is high and suitable to be implemented in a tropical climate country such as Malaysia which is located between at 10 to 70 North latitude and 1000 to 1200 east longitude. Further, Malaysia's direct normal irradiation (DNI) in tropical climate is almost constant throughout a year with the irradiation around 1500 to 2000 kWh/m2. Therefore the aim of this paper is to mathematically calculate the CST field layout in Malaysia in term of thermal efficiency based on cosine efficiency, atmosphere efficiency and mirror efficiency. The preliminary result from this paper shows Malaysia is a suitable location to develop CST with average of atmospheric transmittance efficiency and cosine efficiency of 94% and 63% respectively and the overall optical field efficiency is 52%. In addition, the atmospheric transmittance and cosine efficiency has high value but the efficiency gradually decreases whenever the distance increases. Nevertheless further investigation in term of solar irradiation and raining pattern in Malaysia is needed.